(3GdJQHjI heG djS HJQHjI (B: (3cja dG fQHj CHfGAfGs - (3cQjej, YHO GdYXjes ((3HjQhJs (3OGQ GdgGOjs, 2007)
(3jgOa gPG GdcJGH Edi EMOGK JZjjQ aj feW bQGAJfG ajeG jNU GdJQHjI Ydi GdCUYOI GdKdGKI hHTcd efJXe hefSb(B: (3GdJQHjI HGYJHGQgG eDSSI, Cj fXGekG JQHhjkG jJejR HGdgjcdjI hJfXjeGJ heDSSGJ hELQGAGJ NGUI(B. (3GdJQHjI HGYJHGQgG NWhI GfJGLjI ehdOI Gh JMOjO GdJZjjQGJ GdeWdhH ef GdJQHjI EjLGOgG YfO GdTNU heG gh GdgOa ef hQGA JQHjI GdCTNGU(B. (3GdJQHjI HGYJHGQgG YedjI Cj eG gj GdCSGdjH hGdefGgL GdeWdhH COGDgG dJMbjb GdgOa GdJQHhj NdGd JYGWj GdeQHj eY GdeJQHj(B. (3EfWdGbkG ef gPg GdQDjI jbJQM GdeDda EMOGK fgVI YdejI GfWHGYjI hbjejI ajeG jQJHW HGdeaGgje hGdefGgL GdJQHhjI djJSfi GfJTGd fXGe GdJQHjI hGdJYdje ef GdMGdI GdGUWfGYjI GdGSJgdGcjI(B.s
(3GdfhY (B: (3cJGHs
Keywords: Children; Enfants; (3GdCWaGds